The impact of drying on bioactive compounds of blue honeysuckle berries (Lonicera caerulea var. edulis Turcz. ex Herder) - Senica, Mateja (Array, 2020)
Drying fruit is one of the simplest ways to extend the shelf-life of fruit, especially berries. Both higher temperature and time of heating significantly change the contents of some primary and secondary metabolites in honeysuckle fruit. Differences in their contents arising from different heat treatments were determined with the aid of high-performance liquid chromatography (HPLC) coupled with mass spectrophotometry (MS). The content of sugars showed a small change with drying, while organic acid contents decreased with a longer drying time. Ascorbic acid was totally degraded, regardless of the time or heating temperature. Different phenolic groups responded differently to heat intensity and time of drying. Flavanols were more sensitive to higher temperature than to duration of heating and they decreased by more than 70% at 75 °C. In contrast, the content of hydroxycinnamic acids, increased with drying by more than 75%, regardless of the time and temperature.